Implementation Of The Law Of Evidence: Comparative Country Of Indonesia With The United States Of America - Vifi Swarianata; Fatmawaty Thalib; Fenty U. Puluhulawa; Jufryanto Puluhulawa; Apripari Apripari (Faculty of Law, Kadiri Islamic University (UNISKA) Kediri, 2022)
This research examines the Implementation of the Law of Evidence: Comparative of the State of Indonesia and the United States of America. This study aims to analyze the application of evidence in Indonesia and the United States. This study uses normative research methods. The results of this study explain that there is a comparison between the application of evidence before and during the process in trials between the two countries, but over time and Indonesian law has implemented several processes in evidence that were previously used by the United States. It is hoped that lawmakers in Indonesia will be able to quickly find a new law that will not hinder the process of proof, and will not complicate the judiciary.